Ethical considerations in pediatric chronic illness: The relationship between psychological factors, treatment adherence, and health outcomes. (September 2021) - Rohan, Jennifer M.; Winter, Marcia A.
Abstract: Children, adolescents, and young adults with chronic illnesses are often faced with complicated and burdensome treatments that not only require a great deal of time and energy to manage, but will also likely impact relationships with parents, siblings, and peers. Adolescents and young adults with chronic illness are often impacted by several unique and challenging factors that can ultimately impact health behaviors and treatment outcomes. Working with a psychologist can help to ameliorate these unique challenges, which will positively impact health behaviors and health outcomes. The present paper provides an overview of psychological interventions that were designed to target the unique challenges that are often associated with maladaptive health behaviors and ultimately poor health outcomes. As demonstrated in this commentary, when working with adolescents and young adults who have unique developmental challenges, it is important to deliver multi-faceted intervention approaches that utilize a number of different strategies and frameworks. These eclectic intervention approaches provide a unique opportunity to improve health behaviors during critical developmental periods, including the transition from childhood to adolescence to young adulthood.